Neuropsychological correlates of emotional lability in children with ADHD - Banaschewski, Tobias; Jennen-Steinmetz, Christine; Brandeis, Daniel; Poustka, Luise (The journal of child psychology and psychiatry, 2012)
Background: Emotional lability (EL) is commonly seen in patients with attention-deficit/hyperactivity disorder (ADHD). The reasons for this association remain currently unknown. To address this question, we examined the relationship between ADHD and EL symptoms, and performance on a range of neuropsychological tasks to clarify whether EL symptoms are predicted by particular cognitive and/or motivational dysfunctions and whether these associations are mediated by the presence of ADHD symptoms. Methods: A large multi-site sample of 424 carefully diagnosed ADHD cases and 564 unaffected siblings and controls aged 6-18 years performed a broad neuropsychological test battery, including a Go/No-Go Task, a warned four-choice Reaction Time task, the Maudsley Index of Childhood Delay Aversion and Digit span backwards. Neuropsychological variables were aggregated as indices of processing speed, response variability, executive functions, choice impulsivity and the influence of energetic and/or motivational factors. EL and ADHD symptoms were regressed on each neuropsychological variable in separate analyses controlling for age, gender and IQ, and, in subsequent regression analyses, for ADHD and EL symptoms respectively. Results: Neuropsychological variables significantly predicted ADHD and EL symptoms with moderate-to-low regression coefficients. However, the association between neuropsychological parameters on EL disappeared entirely when the effect of ADHD symptoms was taken into account, revealing that the association between the neuropsychological performance measures and EL is completely mediated statistically by variations in ADHD symptoms. Conversely, neuropsychological effects on ADHD symptoms remained after EL symptom severity was taken into account. Conclusions: The neuropsychological parameters examined, herein, predict ADHD more strongly than EL. They cannot explain EL symptoms beyond what is already accounted for by ADHD symptom severity. The association between EL and ADHD cannot be explained by these cognitive or motivational deficits. Alternative mechanisms, including overlapping genetic influences (pleiotropic effects) and/or alternative neuropsychological processes need to be considered.